The Role of Transparency and Accountability in Increasing Stakeholder Trust in Zakat Fund Management: A Study of LAZIS Central Java - Makhda Intan Sanusi; Sugiyanto; Mohd Badrol Awang (AL-IKTISAB: Journal of Islamic Economic Law, 2026)
The significant potential of zakat in Indonesia is explored through an in-depth investigation of Lazis Jateng’s role as a leading zakat management organization that prioritizes transparency and accountability. In a country with the world's largest Muslim population, zakat serves as a strategic instrument for poverty alleviation and community development. Therefore, professional and responsible management is highly essential to ensure that collected funds comprising Zakat, Infak, and Sedekah (ZIS) effectively support those in need and bridge the widening economic gap within society. This research specifically evaluates how the consistent implementation of transparency and accountability principles by Lazis Jateng directly impacts public trust and the overall volume of donations received by the institution. Using a descriptive qualitative approach, the investigation examines fund management practices through comprehensive interviews with management, detailed document analysis of financial statements, and direct observation of operational workflows. Findings indicate that transparent financial reporting and robust accountability mechanisms significantly enhance stakeholder and donor trust. This increase in trust positively influences donation levels, as muzaki feel assured that their contributions are managed in strict alignment with Sharia principles and reach intended targets efficiently without misappropriation. Furthermore, the work identifies several key challenges, including varying levels of public literacy regarding technical financial reports and the inherent complexities of managing diverse social funds under both religious and state regulations. These findings underscore that transparent and accountable management is a fundamental pillar for building sustainable public trust. By strengthening these aspects, zakat institutions can increase community participation and solidify their role in achieving broader socio-economic goals and social justice in Indonesia, providing valuable insights for future zakat policies.